Find the sum of all positive integers for which the expression above is an integer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 n − 3 should be a prime. otherwise, there exists a prime p ∣ 2 n − 3 , such that p ≤ 2 2 n − 3 < n . So, that p would satisfy p ∣ n ! and, consequently p ∤ 1 5 ( n ! ) 2 + 1 .
Nest, we take p = 2 n − 3 to be a prime.
1 5 ⋅ ( 2 p + 3 ! ) 2 + 1 ≡ 0 ( m o d p ) ⟹ 1 5 ⋅ ( 2 p + 3 ! ) 2 ≡ − 1 ( m o d p ) ⟹ 1 5 ⋅ ( 2 p + 3 ) 2 ⋅ ( 2 p + 3 − 1 ) 2 ⋅ ( 2 p − 1 ! ) 2 ≡ − 1 ( m o d p )
There is a theorem, its name I don't really know, that says for primes p ≥ 3
( 2 p − 1 ! ) 2 ≡ ( − 1 ) 2 p + 1 ( m o d p )
Hence, when p ≥ 3
1 5 ⋅ ( 2 p + 3 ) 2 ⋅ ( 2 p + 3 − 1 ) 2 ⋅ ( 2 p − 1 ! ) 2 ≡ − 1 ( m o d p ) ⟹ 1 5 ⋅ ( 2 p + 3 ) 2 ⋅ ( 2 p + 3 − 1 ) 2 ⋅ ( − 1 ) 2 p + 1 ≡ − 1 ( m o d p )
⟹ 1 5 ⋅ ( 2 p + 3 ) 2 ⋅ ( 2 p + 3 − 1 ) 2 ≡ ( − 1 ) 2 p + 3 ( m o d p )
⟹ 1 5 ⋅ ( 2 p − 1 + 2 ) 2 ⋅ ( 2 p − 1 + 1 ) 2 ≡ ( − 1 ) 2 p + 3 ( m o d p )
note that
2 p − 1 + 2 ≡ − ( 2 p − 1 − 1 ) ( m o d p )
therefore,
⟹ 1 5 ⋅ ( 2 p − 1 − 1 ) 2 ⋅ ( 2 p − 1 + 1 ) 2 ≡ ( − 1 ) 2 p + 3 ( m o d p )
⟹ 1 5 ⋅ ( ( 2 p − 1 ) 2 − 1 ) 2 ≡ ( − 1 ) 2 p + 3 ( m o d p )
Multiplying both sides by 4 2 is legal, since 2 and p are coprimes.
⟹ 1 5 ⋅ ( ( p − 1 ) 2 − 4 ) 2 ≡ 4 2 ⋅ ( − 1 ) 2 p + 3 ( m o d p )
⟹ 1 5 ⋅ 9 ≡ 4 2 ⋅ ( − 1 ) 2 p + 3 ( m o d p )
if p ≡ 1 ( m o d 4 ) , then
p ∣ 1 3 5 − 1 6 = 1 1 9 = 7 ⋅ 1 7
but only 1 7 ≡ 1 ( m o d 4 ) , which gives n = 2 p + 3 = 1 0
if p ≡ 3 ( m o d 4 ) , then
p ∣ 1 3 5 + 1 6 = 1 5 1
1 5 1 ≡ 3 ( m o d 4 ) is a prime and gives n = 2 p + 3 = 7 7
Note that we have considered p ≥ 3 ⟹ n = 2 p + 3 ≥ 3 . n = 1 , 2 both make the fraction an integer.
So, the final sum is 1 + 2 + 1 0 + 7 7 = 9 0